The Rights of Nature in al-Qur’an and Hadith - Nur Arfiyah Febriani; Ahmad Zumaro; Badru Tamam (MAGHZA, 2021)
The purpose of this paper is to find a format that accommodates between human needs, human rights related to nature and the right of nature itself in Quranic and hadith perspectives. By using maudui/tematic interpretation method, the authors found about human ethics is depicted in practical action for all mankind without exception, namely: 1. Appreciating the existence of nature as a fellow creation of God; 2. The wise use of natural resources; 3. Managing the use of natural resources; 4. Prosperate the earth with harmonious interactions; 5. Take care the survival of God s creatures on earth by making efforts to regenerate; 6. Maintain the natural order of the environment as human application of the caliphate function; and 7. Law enforcement for people who do not pay attention to planning; utilization; control; and maintenance; environmental supervision. While Quranic perspective regarding indication of the rights of the nature, including: 1. The right to be respected; 2. The right to a harmonious relationship with fellow creatures; 3. The right to be treated fairly by human beings 4. The right to equal treatment as fellow- creatures of God; 5. The right to worship and obey to God’s command; 6. The right to be rewarded for their existence; 7. The right to grow and develop; 8. The right to seek guidance from God in the form of instinct, to show the function of creation and instinct to survive in life; 9. The right to live within a community (for fauna) and have a leader; and 10. The right to live in pairs.